Glimpses of geometrical principles in malay ornaments / Ruzaika Omar Basaree ... [et al.] - Omar Basaree, Ruzaika; Md Nawawi, Norwani; Md. Khalid, Mohd.Firdaus; Khalid, Mohainee; Ahmad, Mohd Yusof (2012)
The research will examine the link between art and mathematics in the development of Malay ornaments based on the geometrical concepts of symmetry and patterns, which includes the study on the identification of motifs and the significance of repetition, which is a mathematical classification of a two-dimentional repetitive pattern. This paper specifically focuses on a method for classifying Malay ornaments according to mathematical notation system as found in one, the seven frieze patterns to classify the symmetry of the traditional patterns of the Malay woodcarving, which is linear and has symmetry placed like a band of repeated design. Second through the concept of symmetry found in the plane crystallographic group, consisting of seventeen distinct approaches that comprise repetitive patterns, which spread across the plane. This group can be used to categorize traditional Malay songket where the patterns are look at as a whole and not as individual parts. Malay artists, designers and craftsmen usually without realizing it, make use of the practical applications of geometric principles to execute a wide range of geometrical patterns that they use in their work. Most Malay ornamental designs have geometrical basis and no matter how complex they are, will definitely fall into one of the number of symmetry groups of either the frieze pattern or the seventeen patterns of the crystallographic groups. The principle of organization in Malay ornaments are aimed at finding certain solutions for unity, which attempt to create a unified whole out of diverse elements resulting in a balance between harmony and variety.